Electrical system in enabled portable irrigation system - Masturah, Hassan (2022)
An irrigation system is being powered by solar energy. Irrigation systems of agriculture are no longer viable because they waste time and necessitate human labor. Using a solar or photovoltaic device will help you save money and energy (PV). Few or no pollution emissions, such as carbon dioxide or other toxic contaminants, are generated by energy. We can achieve the main purpose of this project is to develop an effective solar water pump system for farmers. By implementation of the hybrid communication system for solar water pump system. Other than that, we can analyze and evaluate the performance and reliability of the system for future documentation and improvement. Finally, we can reduce manpower and save costs as well as help someone who wants to cultivate.